1981 KCPR Auction (1981)
[00:00:02] Beginning of recording, frequent dropouts April 12 1981 [00:00:21] KCPR Supertramp ad, cuts off [00:00:46] Into the Archives section, with esoteric gifts from the basement of the communications buildings [00:04:03] Stu Gold from San Diego calls in [00:04:53] Station 51 mentioned as offering discount [00:08:00] Brian Hackney, Jerry Peek, Donna ? running the auction in the auditorium [00:09:41] Neil Diamond - I Am, I Said [00:11:07] Auction board comes back to discuss new items - Boo Boo Records [00:12:57] Doobie Brothers and Nicolette Larson - Lotta Love [00:13:36] Mock Helicopter traffic report with Frank [00:14:25] Bidding continues with banter from auction board as well as descriptions of items [00:16:35] Jerry Peek, Kristy Keeler mentioned as prizes for an hour with a disc jockey [00:19:54] $900 surpassed in this year's auction [00:20:48] Prize discussion continues - dinner with President Warren Baker [00:30:48] Rusty and Frank from the helicopter [00:31:26] Back to the auction board - candles by Deanna - film processing [00:38:42] Kenny Loggins song [00:39:02] Auction board continues - Rent-A-Car, Station 51, Tortilla Flats, Savings Bonds, Car Wash [00:50:25] Rose Royce - Car Wash [00:50:53] Clearing out the bidding - Kathleen and the savings bond with Rusty [00:52:00] Fleetwood Mac song [00:52:22] Shoutouts to Tom Hiscox, Dave Stein, and other jockeys [00:56:30] Item discussion continues [01:06:31] Jerry Peek, Dave Stein, Mike Kelly, Dave McGarry, Tom Hiscox, Russ Shear, and others thanked [01:08:38] Time is 12:19, event wrap-up continues [01:10:46] End of recording